Biocidal effect of thymol and carvacrol on aquatic organisms: Possible application in ballast water management systems. (August 2018) - Kim, Hyunwoo; Lee, Sungmin; Son, Beomseok; Jeon, Jaewan; Kim, Daehoon; Lee, wonku; Youn, HyeSook; Lee, Jae-Myung; Youn, BuHyun
Abstract: Ballast water is essential for maintaining the balance and integrity of a ship. However, exchanging ballast water resulted in discharging water of different origins in vessel recipient ports, and this may have caused ecosystem disturbance or aquatic pollution. The ballast water management (BWM) system is essential for the purification and disinfection of the ballast water that is taken up. Because current BWM systems widely use biocides for the treatment of aquatic organisms, the biocides may result in unintended toxicity of the discharged ballast water. In this study, we suggested thymol and carvacrol as chemical biocides for BWM systems and investigated their effectiveness using Artemia salina and Escherichia coli . Thymol and carvacrol showed biocidal effects in our study. A combination of these substances showed a synergistic increase in the biocidal effects. Moreover, carvacrol naturally degrades after disinfection, which indicates that natural substances may be promising candidates to increase the efficacy and reduce unwanted side effects of the BWM system. Highlights: Thymol showed specifically high biocidal effect on Artemia salina Carvacrol showed specifically high biocidal effect on Escherichia coli Combination treatment of thymol and carvacrol showed synergistic biocidal effects Carvacrol naturally degraded and lost biocidal effect in 4 days